Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1007/s004679900269
|View full text |Cite
|
Sign up to set email alerts
|

Circulating mediators of proteinuria in idiopathic minimal lesion nephrotic syndrome

Abstract: The pathogenesis of proteinuria in idiopathic minimal lesion nephrotic syndrome (IMLNS) remains to be elucidated. The most-accepted hypothesis is that the increased glomerular permeability to plasma proteins results from the effect of circulating factors on glomerular capillaries. This report critically reviews the current studies that have attempted to isolate and characterize this putative factor(s). Products released from hepatocyte or peripheral blood mononuclear cells or isolated by chromatography from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 40 publications
1
21
0
2
Order By: Relevance
“…17 This response has been interpreted as a consequence of the immunosuppressive effect of glucocorticosteroids. 46 However, the cell and molecular mechanism(s) mediating the effect of glucocorticosteroids on foot process effacement are poorly understood. In cultured podocytes dexamethasone induces activation of nephrin transcription.…”
Section: Discussionmentioning
confidence: 99%
“…17 This response has been interpreted as a consequence of the immunosuppressive effect of glucocorticosteroids. 46 However, the cell and molecular mechanism(s) mediating the effect of glucocorticosteroids on foot process effacement are poorly understood. In cultured podocytes dexamethasone induces activation of nephrin transcription.…”
Section: Discussionmentioning
confidence: 99%
“…A potential candidate for a permeability factor is IL-8/CXCL8. Most studies that assessed this chemokine in INS found increased serum levels in patients during relapse, and normal concentrations in remission (7,8,38). IL-8/CXCL8 was also found to have effects on the metabolism of the glomerular basement membrane, possibly increasing glomerular permeability (7).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been proposed that alterations in the cytokine and chemokine profile of INS patients might contribute to proteinuria and glomerular damage (7,8). Cytokines are a group of proteins produced by several kinds of cells that function as soluble mediators with intercellular signaling functions (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Childhood nephrotic syndrome (NS) 3 is associated with an increase in the permeability across the glomerular filtration barrier due to processes that affect the dynamics and permselectivity of the glomerular filtration barrier. This increased permeability leads to an inability to restrict the loss of protein to Ͻ100 mg/m 2 body surface per day (1 ).…”
mentioning
confidence: 99%